Search for CP violation in [lambda]0b→pK− and [lambda]0b→pπ− decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Esen, Sevda; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physics letters, 2018)
A search for CP violation in Λb0→pK− and Λb0→pπ− decays is presented using a sample of pp collisions collected with the LHCb detector and corresponding to an integrated luminosity of 3.0fb−1. The CP -violating asymmetries are measured to be ACPpK−=−0.020±0.013±0.019 and ACPpπ−=−0.035±0.017±0.020, and their difference ACPpK−−ACPpπ−=0.014±0.022±0.010, where the first uncertainties are statistical and the second systematic. These are the most precise measurements of such asymmetries to date.
Im Titel ist "lambda" als griechischer Buchstabe dargestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, N. Skidmore, S. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 28.05.2019